Clifford and the Missing Beach Ball - Fay, Sonali (New York : Scholastic, Inc., 2002)
Clifford, T-Bone, and Cleo are ready for some fun in the sun! T-Bone is especially eager to play with his brand-new beach ball. But when a big wave hits the shore, his new toy is washed away! The dogs look for the ball and uncover all kinds of beach inhabitants--crabs, seashells, seaweed, starfish, and more. When T-Bone finally finds his prized possession, its with a little help from his ocean friends.
Keywords: Childrens fiction